Visualization of Tomato Growth Based on Dry Matter Flow. (19th March 2017) - Li, Hongjun; Zhang, Xiaopeng; Meng, Weiliang; Ge, Lin
Abstract : The visualization of tomato growth can be used in 3D computer games and virtual gardens. Based on the growth theory involving the respiration theory, the photosynthesis, and dry matter partition, a visual system is developed. The tomato growth visual simulation system is light-and-temperature-dependent and shows plausible visual effects in consideration of the continuous growth, texture map, gravity influence, and collision detection. In addition, the virtual tomato plant information, such as the plant height, leaf area index, fruit weight, and dry matter, can be updated and output in real time.